RESULTS OF NUTRITION ANALYSIS OF FREQUENTLY ILLNESS PRESCHOOL CHILDREN DURING THE WINTER SEASON - Nizom J. Ermatov; Shovkatjon M. Khaydarov (Central Asian Journal of Medicine, 2024)
This article provides a hygienic analysis of the composition of the daily diet of children of preschool age with frequent illnesses. 1,250 children between the ages of 3 and 7 were taken, who were brought up in controlled state preschool organizations. We analyzed the nutrition of schoolchildren of the preschool organization in the winter season of the year. The structural structure of the daily diet of children was established on the basis of the requirements of sanitary norms and rules No. 0016-21, and the quantitative indicators of the chemical composition of the daily diet and its number and quality indicators were evaluated on the “Chemical composition of food products”. Conclusion. When the content of protein, fat, carbohydrates, vitamins and minerals in the food products consumed by children in public preschool organizations during the winter season was estimated, it was found that the daily diet did not correspond to hygienic requirements.